Business Plan : C’Best Enterprise / Aimi Syazwani Ghazali ... [et al.] - Ghazali, Aimi Syazwani; Ismail, Fidiatun; Azmi, Nadiah; Shaari, Noraniza (2008)
This business plan is generally explain about the step to build a business company. This business plan is focusing on pre preparation of C’Best Enterprise before this business can real operate in future. It is compulsory to the entrepreneur to make their own business plan in order to make sure that they gain profit from their own business.This business plan had followed all the required format of a business plan. In the first chapter, this business plan gives an overall introduction to the proposed business venture. Some item that had been covered are name of the company, nature of business, industry profile, location of the business, date of business commencement, factors in selecting the proposed business and future prospects of the business. In the second chapter, we are discussed on the purpose of making business plan.We stated the five proposes in this chapter. In the third chapter, we mention about all the details of the company background. We stated the name of the company, business address, correspondence address, telephone number, form of business and all the related information about this company. In the fourth chapter, we listed our partners’ background. The information here serves to highlight the business partners’ business credibility as well as our ability to manage this company. In the fifth chapter, we showed our location of the business. The purpose of this section is to provide additional information on the location of our business premise. As to make reader clearly determine our location, we provide the physical location plan. Chapter six, which is one of the important chapters, we discussed on our administrative plan. It mention about business routines are maintain and controlled. This section has to manage the overall business objective and goals. We are discussed on the task and responsibilities of employees. Apart from that, we also stated our administrative budget in this chapter. The next chapter, which is chapter seven, is discussed on marketing plan. In order to meet customer needs and wants, we have made sure that our business plan has incorporated a well-structured marketing plan. This marketing plan explains how customers’ needs and wants will be met. It also mentioned how our marketing effort will link with the operational, administration and financial plans of the same venture. In the other chapter, which is operation plan, we explained our operation process in detail. We shown this by stated the process flow chart to make them easy to understand. The other important chapter is related to the financial plan. This financial plan acts as a point where all the financial information in the administrative, marketing and operation plans are collated and summarized to give a picture of how much the business will cost to run. By referring to this chapter, we could determine whether this business is profitable or not. As to conclude our business plan, we gave a brief summary of the main contents, the main purpose of this business plan and the other point to bring our business plan to a close.